Rapporto 1/2021 – L’impiego dell’intelligenza artificiale nell’attività di CONSOB, AGCOM e ARERA - Chiti, Edoardo; Marchetti, Barbara; Rangone, Nicoletta; Togna, Tiziana; Limosani, Alessandra; Frega, Giuseppe; Deriu, Paola; Ragucci, Gennaro; Lo Schiavo, Luca; Lazza, Luca (BioLaw Journal - Rivista di BioDiritto, 2021)